2011
DOI: 10.1080/00221686.2010.535700
|View full text |Cite
|
Sign up to set email alerts
|

An ordinary differential equation for velocity distribution and dip-phenomenon in open channel flows

Abstract: International audienceAn ordinary differential equation for velocity distribution in open channel flows is presented based on an analysis of the Reynolds-Averaged Navier-Stokes equations and a log-wake modified eddy viscosity distribution. This proposed equation allows to predict the velocity-dip-phenomenon, i.e. the maximum velocity below the free surface. Two different degrees of approximations are presented, a semi-analytical solution of the proposed ordinary differential equation, i.e. the full dip-modifie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(50 citation statements)
references
References 22 publications
2
43
0
Order By: Relevance
“…Vanoni (1941) also suggested that the dip phenomenon is observed at the corner zones even for the wide open channels where the velocity profile deviates from the log-wake law. Absi (2011) suggested an ordinary differential equation for velocity distribution and dip-phenomenon in open channel flows. Rodríguez and García (2008) studied the effect of secondary flow occurred in the corner region of a narrow open channel.…”
Section: Introductionmentioning
confidence: 99%
“…Vanoni (1941) also suggested that the dip phenomenon is observed at the corner zones even for the wide open channels where the velocity profile deviates from the log-wake law. Absi (2011) suggested an ordinary differential equation for velocity distribution and dip-phenomenon in open channel flows. Rodríguez and García (2008) studied the effect of secondary flow occurred in the corner region of a narrow open channel.…”
Section: Introductionmentioning
confidence: 99%
“…Absi (2011) modified this model to predict the velocity-dip-position for validating his proposed velocity model full dip-modifiedlogwakelaw (fDMLW-law). Bonakdari et al (2008) critically analyzed both the models of Wang et al (2001) and Yang et al (2004) for small channel aspect ratio.…”
Section: Introductionmentioning
confidence: 99%
“…A Modified Log-Wake Law (MLWL) is proposed by Guo and Julien (2003) and Guo et al (2005) which is applicable to velocity data measured in both pipe and open channel flow in laboratory and field. Based on the analysis of the Reynoldsaveraged Navier-Stokes (RANS) equations and a log-wake modified eddy viscosity distribution, Absi (2011) proposed an ordinary differential equation for velocity distribution to predict the velocity-dipphenomenon. Bonakdari et al (2008) analyzed Navier-Stokes equations and suggested a new formulation of the vertical velocity profile in the center region of steady fully developed turbulent open-channel flows.…”
Section: Clauser Methods (U*l)mentioning
confidence: 99%